Competency Assessment in Nutrition and Dietetics : the CAND Resource. - Palermo, Claire; Capra, Sandra; Ash, Susan; Beck, Eleanor; Truby, Helen; Jolly, Brian (Office for Learning and Teaching, 2014)
Resource emanating from a project that engaged the nutrition and dietetics education community in exploring the challenges in assessment of entry-level competence and how to support best practice assessment of competence across three domains of practice: individual case management, food service management and community/public health nutrition. This resource was developed to support educators in designing and implementing best-practice assessment for nutrition and dietetics.